(untitled) (Research, Society and Development, 2020)
The use of pesticide and the current model of agricultural development is responsible for impacts, environmental, and health damage. For grain production to be satisfactory, the correct use of management techniques is a decisive factor in the development and harvesting of grains. The crop and consumption of white oats have become evident in recent years due to its versatility, however, it is sensitive to environmental variations affected by fungal diseases. This research aimed to analyze scientific productions published in national and international journals on white oats crop with reduced pesticide use, crop sustainable assurance to the environment, and food security. From the question: "What has been published in national and international literature about white oat crop for human consumption with reduced fungicide use ?". With the following descriptors: (Fungicide AND “Avena sativa”) in the databases WEB OF SCIENCE (main collection) and SciVerse Scopus (SCOPUS), SCIENCE DIRECT and MENDELEY. A total of 312 articles found and 15 selected and read in full. The results indicate that regardless of the use or not of fungicide, the genetic resistance of cultivars to fungal diseases is the decisive factor for cultivation.